Phytochemical and antipyretic potential of ethanolic leaf extract of Heliotropium indicum l. - Basak, Mrinmoy; Dey, Biplab Kumar (Creative Pharma Assent, 2016)
In the present study, the ethanolic leaf extract of Heliotropium indicum L (H. indicum L) was investigated for phytochemical screening and antipyretic activity in rats using Brewer's yeast induced Pyrexia. The leaves of H. indicum were collected from different part of Assam and cut into small pieces and shade dried. The dried powdered leaves (100 gm) were extracted in a Soxhlet apparatus by using 95% ethanol. Phytochemical screening has been done by standard procedure and showed the presence of alkaloids, glycoside, carbohydrate, phytosterol, flavonoids and saponins and absence of fixed oil and gums-mucilage. Albino rats weighing (200-250g) were taken for the experiment divided into four groups of six animals each. Group 1 received 3% aqueous suspension of gum Acacia (1ml/200g) as vehicle orally, group 2 and group 3 received ethanolic leaf extract of H. indicum 250 and 500 mg/kg with 3% aqueous suspension of gum Acacia orally and the group 4 served as standard received paracetamol 25 mg/kg with 3% aqueous suspension of gum Acacia orally. The subcutaneous injection of yeast suspension markedly elevated the rectal temperature after 18h of administration. Treatment with H. indicum extract at a dose of 250, 500 mg/kg decreased the rectal temperature of the rats in dose dependent manner. This effect was maximal at dose of 500 mg/kg and it caused significant lowering of body temperature (P< 0.01) up to 4 hour after its administration. The antipyretic effect started as early as 1h and the effect was maintained for 4h, after its administration. Both the standard drug paracetamol 25mg/kg and tested drug H. indicum extract were significantly reduced the yeast elevated rectal temperature, at 2nd, 3rd and 4th hour compared to control group.